Women health and disease pattern in the rural areas of Bangladesh: a case study on Haimchar upazila under Chandpur district (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present research has undertaken to understand the women health scenario in a remote rural char land of the country and their health awareness with hygienic practices. Most of the women in the study area were found illiterate and not fully conscious about health and health care aspects. The overall health condition of women in the study area was found very poor and affected various diseases from lack of personal attention and adequate health care. It is evident that most of the women age ranging from 26 to 45 in the study area were the most sufferer of different number of diseases like fever, diarrhoea, skin diseases, asthma, reproductive tract infections (RTI) and various gynecological diseases. It was also identified that, water and sanitation related diseases are very common among the women of the study area which may be the result of using unsafe water and unhygienic sanitation practices.J. Asiat. Soc. Bangladesh, Sci. 40(1): 27-37, June 2014